2014
DOI: 10.1002/2014jd022100
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a rocket‐triggered lightning flash with large stroke number and the associated leader propagation

Abstract: A negative lightning flash with 16 leader-return stroke sequences, triggered in the summer of 2013 using the classical rocket-and-wire triggering technique, was examined with simultaneous two-dimensional (2D) imaging of very high-frequency (VHF) radiation sources, channel-base current measurement, broadband electric field waveforms and high-speed video images. A total of 28.0 C negative charge was transferred to ground during the whole flash, and the charge transferred during the initial stage was 4.9 C, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 24 publications
2
37
0
Order By: Relevance
“…The results are compatible with those presented by Yokoyama et al () and Gao et al () for negative CG lightning. It is interesting to note that the estimated two‐dimensional speeds are still similar to those reported for positive leaders of negative upward lightning, 0.081 × 10 6 m/s according to Wang et al (), and of negative rocket triggered lightning, 0.038 × 10 6 m/s to 0.21 × 10 6 m/s in the works by Sun et al () and Biagi et al (), respectively.…”
Section: Discussion On Specific Features Of Upward Leaders In Naturalsupporting
confidence: 82%
See 1 more Smart Citation
“…The results are compatible with those presented by Yokoyama et al () and Gao et al () for negative CG lightning. It is interesting to note that the estimated two‐dimensional speeds are still similar to those reported for positive leaders of negative upward lightning, 0.081 × 10 6 m/s according to Wang et al (), and of negative rocket triggered lightning, 0.038 × 10 6 m/s to 0.21 × 10 6 m/s in the works by Sun et al () and Biagi et al (), respectively.…”
Section: Discussion On Specific Features Of Upward Leaders In Naturalsupporting
confidence: 82%
“…In three other events, the pulses observed in the measured current were correlated with the pulses of the close electric field. Sun et al () identified VHF sources at the tip of a propagating upward positive leader in a sole negative triggered lightning and also observed pulses of current in the initial continuous current. Though no correlation was observed between the pulses of current and VHF radiation, they presumed a stepwise propagation of the positive leader.…”
Section: Discussion On Specific Features Of Upward Leaders In Naturalmentioning
confidence: 99%
“…The signals from each antenna were bandpass filtered to 25-90 MHz and recorded with 16 bit resolution at a sampling rate of 200 MHz continuously for 2 s. The recorded time series waveforms were postprocessed utilizing generalized cross-correlation time delay algorithm [Sun et al, 2013[Sun et al, , 2014Stock et al, 2014], applied to sequences of overlapping data segments from the time series waveforms. It consisted of three broadband VHF discone antennas placed at the vertices of an equilateral triangle 20 m on each side.…”
Section: Methodsmentioning
confidence: 99%
“…The last gray panel shows the overlapped locations of all radiation sources of F1302. Detailed propagating characteristics of each leader have been discussed in Sun et al (). Here we show them again to facilitate our understanding of what happened inside the cloud when CPT occurred.…”
Section: Results and Analysismentioning
confidence: 99%
“…The channel base current, VHF radiation and channel mapping, fast E‐field, and high‐speed video images in this study were obtained during a classical rocket‐triggered cloud‐to‐ground lightning flash F1302 in SHAndong Triggering Lightning Experiment (SHATLE). The flash F1302 was triggered at 21:37:12 UT on 2 August 2013 and had a large return stroke number of 16 (Lu et al, ; Sun et al, ). The satellite image of the SHATLE is shown in Figure .…”
Section: Methodsmentioning
confidence: 99%